Frankenstein: The Dead Town - Book 5 - Koontz, Dean R. 1945- (Dean Ray) (New York : Bantam Books, 2011)
The last of the survivors in Rainbow Falls, Montana, band together to brave the onslaught of the creatures set loose upon the world, discovering the full scope of Victor Frankenstein's nihilistic plan to remake the future.
Keywords: Frankenstein, Victor (Fictitious character) -- Fiction; Frankenstein's monster (Fictitious character) -- Fiction; Scientists -- Fiction; Monsters -- Fiction; Montana -- Fiction; Horror fiction